An Analysis of Electronic Health Records in US Medical Practice by a Physician - Irina V. Angel (Public Health, 2025)
This commentary presents a point of view on how the arrival of electronic health records (EHR) in the United States (U.S.) has changed physicians’ practice. EHR implementation has pros and cons. EHR systems have been a great asset during the pandemic and help with efficiency, safety, and cost reduction. Despite their benefits, healthcare providers and organizations still face challenges, including usability and interoperability across systems, contributing to physicians’ burnout. Can physicians adopt new technologies and adapt to current challenges? Is it the right time for physicians to stop being observers and become active participants in the process of healthcare innovation and implementation?